Poly(butylene disulfide) and poly(butylene tetrasulfide): Synthesis, cure and investigation of polymerization yield and effect of sulfur content on mechanical and thermophysical properties. (3rd June 2021) - Sheydaei, Milad; Edraki, Milad; Javanbakht, Shiva; Alinia-Ahandani, Ebrahim; Soleimani, Mahdieh; Zerafatkhah, Alireza
Abstract: In this work, two polysulfide polymers were synthesized by use of 1, 4-dichlorobutane and aqueous sodium disulfide or sodium tetrasulfide. The polymers were cured at 85 °C. The structural characteristics of non-cured and cured samples were identified by Raman and FT-IR spectroscopy. The morphological and the thermophysical properties of all samples were investigated by X-ray diffraction (XRD) and differential scanning calorimetry (DSC). Also, the mechanical properties and hardness of all samples were investigated by tensile test and Shore A. Moreover, the effects of temperature and ethanol on polymerization were investigated. Aqueous monomers were characterized by UV-VIS-NIR spectroscopy. The molecular weight of the synthesized samples was determined by 1 H NMR spectroscopy. The results showed that, before curing, poly(butylene tetrasulfide) (PBTS) due to amorphous structure does not have a melting peak and both polymers have a very low glass transition temperature. Without ethanol, no polymerization reaction takes place. Before curing, poly(butylene disulfide) (PBDS) is brittle and PBTS has an elastomeric behavior, but after curing PBDS also behaves as elastomer. The curing times of the two polymers are close to each other, but their mechanical properties and hardness are different. Graphical Abstract: